On Some Properties Of 0-Expansions Of Real Numbers Related To Regular Continued Fraction Expansion - Muhammad, Khairun Nisak (2022)
This introductory chapter discusses background study of continued fraction expansions of real numbers which highlights the development of various types of continued fraction expansions. Apart from the regular continued fractions, this chapter also reviews some other variants of it such as optimal continued fraction (OCF) (Bosma, 1987), nearest integer continued fraction (NICF) (Tong, 1992), Engel continued fraction (ECF) (Hartono et al., 2002),